2004
DOI: 10.1128/mcb.24.8.3157-3167.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamics of Swi6 in Yeast: Evidence for a Stochastic Model of Heterochromatin

Abstract: The mechanism for transcriptional silencing of pericentric heterochromatin is conserved from fission yeast to mammals. Silenced genome regions are marked by epigenetic methylation of histone H3, which serves as a binding site for structural heterochromatin proteins. In the fission yeast Schizosaccharomyces pombe, the major structural heterochromatin protein is Swi6. To gain insight into Swi6 function in vivo, we have studied its dynamics in the nucleus of living yeast. We demonstrate that, in contrast to mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
77
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 56 publications
13
77
0
Order By: Relevance
“…We suspect that the ability of pot1D and tpz1D to bypass dcr1D is due to the loss of telomere and subtelomere sequences, which consequently affects silencing at telomeres. Such a model is consistent with recent imaging and biochemical studies showing that HP1/ Swi6 proteins are highly mobile on chromatin (Cheutin et al 2003(Cheutin et al , 2004Festenstein et al 2003;Sadaie et al 2008).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We suspect that the ability of pot1D and tpz1D to bypass dcr1D is due to the loss of telomere and subtelomere sequences, which consequently affects silencing at telomeres. Such a model is consistent with recent imaging and biochemical studies showing that HP1/ Swi6 proteins are highly mobile on chromatin (Cheutin et al 2003(Cheutin et al , 2004Festenstein et al 2003;Sadaie et al 2008).…”
Section: Discussionsupporting
confidence: 78%
“…H3K9me allows for the binding of heterochromatin protein 1 (HP1), which compacts chromatin through its self-association and the recruitment of other chromatin-modifying activities (Grewal and Jia 2007). Although heterochromatin has traditionally been considered silent, stable, and static, recent biochemical and imaging studies show that the binding of HP1 proteins to heterochromatin regions is surprisingly dynamic (Cheutin et al 2003(Cheutin et al , 2004Festenstein et al 2003;Sadaie et al 2008). Moreover, although heterochromatin normally excludes the transcriptional machinery, the DNA repeats within heterochromatin are transcribed, and the transcripts are processed by the RNAi pathway into siRNAs, which target histone-modifying complexes to repetitive DNA elements (Moazed, 2009;Lejeune and Allshire 2011;Castel and Martienssen 2013).…”
mentioning
confidence: 99%
“…However, several studies have now suggested that this view might be an oversimplification. Not only do various high-molecular weight probes and proteins readily enter heterochromatin [10][11][12][13][14] , but also transcription of repetitive sequences by specific RNA polymerases is required for methylation of H3K9 and heterochromatin assembly 43 . It is possible that bursts of transcription occur particularly during S-phase offering an explanation to reconcile the conflicting concepts of transcriptional repression and active transcription in heterochromatin [44][45][46] .…”
Section: Resultsmentioning
confidence: 99%
“…The view of higher-order structure as a regulator of accessibility, however, has been challenged by measurements of diffusional motilities of nuclear proteins. Proteins can readily diffuse even into highly condensed heterochromatin [10][11][12] , and inert diffusion probes of the size of large protein complexes readily entered condensed chromatin 13,14 . Similarly, a recent study of genome-wide DNA accessibility in Drosophila using M.SssI methylation footprinting questions the view of greatly reduced accessibility of heterochromatin: DNA in chromatin carrying H3K9me2 seems to be as accessible as the rest of the genome 15 .…”
mentioning
confidence: 99%
“…Recently published FRAP data on HP1-gfp transfected cells have shown that all forms of HP1-gfp exhibit rapid dynamics, with the bulk of the fluorescence returning to the bleached area within seconds (36,45,47,48). To find out whether this holds in our experimental system, we performed FRAP and inverse FRAP studies on transiently transfected HeLa cells.…”
Section: ) Were Left Behind (Compare Lanes Inp and Nb)mentioning
confidence: 99%